Low test-weight sorghum for growing-finishing swine - J A Hansen; R C Thaler; Robert D Goodband; Jim L Nelssen; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1990)
Two growth studies were conducted to determine the effects of substituting lower test-weight sorghum (35 lb/bu as LOW or 45 lb/bu as MED) for normal test-weight sorghum (55 lb/bu NORM), in growing and finishing swine diets. One-hundred twelve pigs (50 lb initial wt) were fed for 28 d in the grower study and 80 pigs (120 lb initial wt) were fed for 51 d in the finisher study. Diets were formulated to contain .80 and .65% lysine for the grower and finisher trials, respectively, using NORM and soybean meal; LOW and MED were substituted on a wt/wt basis for NORM. The fourth treatment evaluated was a 50:50 (wt:wt) blend of LOW/NORM. Apparent dry matter and nitrogen digestibility were determined on d 14 of the grower trial using chromic oxide as a nondigestible marker. In the grower study, pigs fed the NORM or MED had similar growth rates, daily feed intakes, and feed conversions. However, pigs fed the LOW diet tended to grow slower and convert feed to gain less efficiently than pigs fed either the NORM or MED diets. Similarly, pigs fed the LOW/NORM blend tended to perform at a level intermediate to pigs fed the MED and LOW diets. Dry matter and N digestibilities paralleled the numeric trends noticed in the performance data, and significant differences were detected between NORM or MED and the LOW or LOW/NORM. In the finishing trial, pigs fed the NORM or MED gained at similar rates and had similar feed efficiencies, but pigs fed the LOW or blend had poorer feed/gain and slightly poorer growth rates. In a companion study, chicks fed the sorghums had linear reductions in growth rate and feed conversions when fed diets containing reduced test-weight sorghum. Overall, LOW sorghum can be expected to cause a 5 to 7% reduction in gains and a 7 to 12% reduction in feed/gain when fed to growing and finishing pigs. Similar reductions are observed for chicks (6 to 7% reduction in growth rate; 4 to 5% reduction in feed/gain). Medium sorghum has an equal feeding value to NORM sorghum for both growing and finishing swine and a slightly lower feeding value for chicks.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Sorghum; Test weight; Damaged; GF; Performance